Peningkatan Pengetahuan Literasi Profesi dan Kompetensi Akuntan Pada Siswa XII SMKN 1 Waringinkurung - Sukiyaningsih, Tri Wahyuni; Hasanah, Ade Nahdiatul; Agnia, Ila Lailatul; Rifaldi, Irfan; Juwita, Salsadilah; Hasanah, Siti Alivia (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
Increasing professional literacy and competence of accountants in non-accounting vocational students who study accounting certainly requires a touch of more knowledge related to the profession in the field of accounting and the process of obtaining state accountant certification. Through the method of concrete and interactive exposure to students directly (face to face) outside of study hours will provide significant and positive improvement results. Based on the results of comparison of pre-test and post-test resulted in an increase of 1 level, where the pre-test produced the average value of student knowledge XII OTKP SMKN 1 Waringinkurung at Level D with a statement (lack of Understanding/know). While the results of the post test after being given the exposure of professional literacy and competence of accountants, the average value of the student's knowledge increased at the level of C with a statement (enough to understand/know). The end result of this PkM activity is an increase in the repertoire of knowledge of non-accounting vocational school students in studying the material of the profession and the competence of accountants so that they can be practiced in the future in achieving a professional career in accounting.